Navigating Women's Low Desire: Sexual Growth and Destiny Beliefs and Couples' Well-Being. Issue 9 (22nd November 2021) - Raposo, Stephanie; Rosen, Natalie O.; Corsini-Munt, Serena; Maxwell, Jessica A.; Muise, Amy
ABSTRACT: People's beliefs about how to maintain sexual satisfaction have been associated with how they navigate sexual differences, but research has yet to explore the consequences of these beliefs for couples facing a distressing sexual issue. The current research extends past work on sexual growth beliefs (i.e., the view that sexual satisfaction requires continuous effort to maintain) and sexual destiny beliefs (i.e., the view that sexual satisfaction is the result of natural sexual compatibility with a partner) to couples for whom these beliefs might be especially consequential – those coping with sexual dysfunction. In a dyadic longitudinal study of 97 couples coping with women's clinically significant low desire and arousal, we tested how sexual growth and destiny beliefs are associated with sexual, relationship, and personal well-being. We found that endorsing greater sexual growth beliefs was associated with higher sexual desire for both partners, whereas, with some exceptions, endorsing greater sexual destiny beliefs was linked to lower sexual desire and relationship satisfaction, more conflict, and more depressive and anxious symptoms. However, these effects did not persist one year later. Our findings highlight the implications of sexual growth and destiny beliefs for both couple members when navigating a chronic sexual difficulty.